Child abuse: perception and knowledge by Public Health Dentistry teams in Brazil - Mariana Dalledone; Ana Paula Borges Paola; Gisele Maria Correr; Eduardo Pizzatto; Juliana Feltrin Souza; Estela Maris Losso (Universidade Estadual de Campinas, 2015)
Aim: To evaluate the experience, knowledge and attitudes of dentists and oral health technicians (OHTs) who work in Basic Health Units in the city of Curitiba, PR, Brazil, regarding cases of abuse against children and adolescents. Methods: In this observational study, three hundred eighty-three questionnaires (validated for Brazilian Portuguese) were sent to dentists and OHTs who work in public health units. The response rate was 38.12% (n = 146) for dentists and 40% (n = 77) for OHTs. Results: The mean age of the dentists was 40±8.29 years, and 53.43% treated more than 10 children per week. The OHTs' mean age was 45.39±9.71 years, and 62.35% attended to more than 10 children per week. Although the dentists perceived 185 suspected cases of maltreatment, only 35.67% were reported to authorities. In the OHT group, 22.08% were reported to authorities. Sixty-eight dentists (47%) and 11 OHTs (14.28%) reported having treated at least one case of orofacial trauma in the previous 6 months, totalizing 166 orofacial traumas. About the mechanism for reporting suspected cases, 83% of the respondents knew how to report. Over 50% of the responses concerning why the professionals did not report cases of physical violence against children included fear of retaliation and difficulties in diagnosis. Conclusions: Suspected cases of maltreatment against children and adolescents are underreported. More information is required to recognize suspected maltreatment cases and notify authorities.